2016
DOI: 10.1016/j.shaw.2016.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Proposal for an Evaluation Method for the Performance of Work Procedures

Abstract: BackgroundNoncompliance of operators with work procedures is a recurrent problem. This human behavior has been said to be situational and studied by many different approaches (ergonomic and others), which consider the noncompliance with work procedures to be obvious and seek to analyze its causes as well as consequences.MethodsThe object of the proposed method is to solve this problem by focusing on the performance of work procedures and ensuring improved performance on a continuous basis.ResultsThis study has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…As a rule, there is a need to involve external experts -professional consultants from outside during certification. In modern conditions, there occur very common situations, when the basic conditions are set by a client, which is a commercial organization, whereasthe organization of certification system is set up directly by the consultants [22,23].…”
Section: Resultsmentioning
confidence: 99%
“…As a rule, there is a need to involve external experts -professional consultants from outside during certification. In modern conditions, there occur very common situations, when the basic conditions are set by a client, which is a commercial organization, whereasthe organization of certification system is set up directly by the consultants [22,23].…”
Section: Resultsmentioning
confidence: 99%
“…Few studies aimed to understand the constraints on workers' capabilities and their needs based on the conditions of their work environment (Report et al., 2001; Jaffar and Lop, 2011a,b; Moura et al., 2017a,b; Techera et al., 2018). Another study indicated that the effect of safety compliance on safe work practices was predicted by the effects of both workload and extra rules (Mohammed et al., 2016; Leung et al., 2016). These studies confirmed the need to address the margin of a personal lifetime to serve the important life-issues and minimize the associated tension.…”
Section: Introductionmentioning
confidence: 99%
“…Stress-based tension is another exogenous factor. It is affected by communication, physical work environment, and margin of a personal lifetime based on the evidences summarized in the literature section (Report et al., 2001; Hobbs and Williamson, 2003; Sheridan, 2008; Leung et al., 2010; Jaffar and Lop, 2011a,b; Ganguly, 2011; Shi and Inoue, 2012; Bowen et al., 2014; Amorim and Pereira, 2015; Blazsin and Guldenmund, 2015; Zhou and Jiang, 2015; Bergheim et al., 2015; Moreno and Cavazotte, 2015; Praino and Joseph, 2016; Leung et al., 2016; Mohammed et al., 2016; Yoon et al., 2016; Jepson et al., 2017; Moura et al., 2017a,b; Liang et al., 2018; Oah et al., 2018; Techera et al., 2018).…”
Section: Introductionmentioning
confidence: 99%